Function and Pedagogical Value in Banjet Mask Group Performance Abah Pendul - Rudi Hartono; Sukmawati Saleh (Universitas Negeri Medan, 2023)
Topeng Banjet is one of the distinctive arts that is a heritage of art and culture that has traditionally existed and developed in Karawang Regency since the 1920s. The focus of the study is on Topeng Banjet Group Sinar Pusaka Karawang in Tempuran District and commonly known as Topeng Banjet Abah Pendul. The purpose of this study is to reveal the function of art and pedagogical values contained in the Topeng Banjet performance process. The performance is carried out through a process of stages namely; ngukus, songs and music, tap tilu dance, jokes and plays on an open field. The study is based on descriptive analytical qualitative data collected by observation, interview and documentation. This study includes pedagogical functions and values; education, educational content and educational tools. The purpose of education is required where every citizen or community is required to learn and practice mastery sourced from local cultural traditions. The Topeng Banjet performance originally functioned as a thanksgiving for the harvest. The Topeng Banjet Group Sinar Pusaka Warna has experienced several changes in leadership from the 1920s until now; as an educational tool, habits, recommendations, monitoring, taboos, and consequences are used in the implementation process at the beginning of the performance; ngukus or rituals at the beginning to ask the Almighty for all the blessings of the harvest and the smooth running of the show after praying the players sprinkle flower water on the musical instruments used and rub the smoke of burning incense all over the face and body of the players followed by musical entertainment, songs, dances, and dramas.